Effect of OA-ZnSe nanoparticles incorporation on the performance of PVK organic photovoltaic cells. (15th June 2017) - Benchaabane, Aida; Ben Hamed, Zied; Telfah, Ahmad; Abderrahmane Sanhoury, Mohamed; Kouki, Fayçal; Zellama, Kacem; Bouchriha, Habib
Abstract: The impacts of the Oleic Acid capped ZnSe (OA-ZnSe) nanoparticles content variation on the microstructural and electrical properties of the ITO/PVK:OA-ZnSe/Al hybrid cell have been investigated by using a combination between the FTIR and the electrical measurements. Based on the J-V characteristics of studied hybrid cell in dark, the conduction mechanism for voltages lower than 1.5 V follows the Richardson–Schottky law. On voltages above 1.5 V, the J–V characteristics can be successfully modeled by other theories such as the space-charge limited current (SCLC) or the trap charge limited current (TCLC). Under white light illumination, the J–V characteristics are clearly affected by the incorporation of OA-ZnSe nanoparticles, indicating a significant improvement of the photovoltaic cell parameters, in particular the conversion efficiency which increases 12-fold compared to the cell based on non-doped PVK. The effective photocurrent density Jph of the hybrid cells with different OA-ZnSe contents are also considered.